The Effect of Tourism to Transnational and Conventional Crimes in Nusa Penida, Klungkung - Bali - I Ketut Mertha; Gede Made Swardhana (Sociological Jurisprudence Journal, 2018)
Not all tourism has a positive impact sometimes have a negative impact. Events about tourists as victims of crime is also a lesson for us, but not infrequently also the tourists who visit Bali also there is a crime for the sake of survival and life. Many cases that happened, such as cases of money changer money changerSabtu February 4, 2017 and the cases that occurred Police resort of Klungkung area that also oversees Nusa Penida such as crime theft motor, gold theft, porn video penggugah, and others. In addition to the negative impacts found above, tourism is particularly vulnerable to transnational crime issues that not only undermine the existing tourism but have penetrated the international region. This research is important as a crime prevention effort in Klungkung Bali, and especially in Nusa Penida. By knowing the frequency of transnational crime and conventional crimes that occurred in the Klungkung Polreschief, Bali and the influence of tourism visits with crimes that occurred in the Klungkung Police area, especially in Nusa Penida can be seen the development of crimes that occurred and efforts to overcome them. This research uses criminological juridical approach, which is analytical descriptive with unstructured interview technique and processed and analyzed with qualitative analysis model. Data is processed and analyzed by systematically arranging data, identified, categorized or classified, connected between one data with other data, interpretation to understand the meaning of data in social situations, and then done the interpretation from the researcher's perspective after understanding the overall data quality.